Who is buried in Playfair's Grave?. Issue 5 (12th October 2017) - Spence, Ian; Fenn, Colin R.; Klein, Scott
Abstract: Ian Spence, Colin R. Fenn and Scott Klein go in search of the final resting place of William Playfair, who devised many of the statistical graphics in use today